(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article focuses on three aspects of students ’reading literacy on the basis of the international PIRLS program developed with the aim of increasing students’ reading literacy, improving their development and helping them acquire reading skills, evaluating their students ’ reading abilities, evaluating four types of comprehension process, studying reading objectives and comprehension processes, The PIRLS study highlights the importance of assessing the two types of learning that students use more than others outside the classroom and school and the introduction of this into the national education system today